History of the stock status and fishery regulation for red king crab Paralithodes camtschaticus in the waters of Primorye - A. G. Slizkin; O. Yu. Borilko; E. E. Borisovets; I. S. Chernienko; O. B. Tkacheva (Известия ТИНРО, 2025)
Development of the red king crab Paralithodes camtschaticus fishery in the waters of southern Primorye is overviewed. Methods of catching and processing the catch are described. Reasons for periodic reduction in density of the crab aggregations and total stock are analyzed. Dynamics of the crab fishery between the periods of its prohibition is traced since the early 20th century to the present days and duration of the banning is determined, with particular attention to the dramatic changes which led to the ban of fishery because of the stock decreasing.